Baby Yoga’s Effect of Bounding Attachment - Silvia Ari Agustina; Reni Merta Kusuma (LPPM Universitas Duta Bangsa Surakarta, 2019)
Yoga can not only be done by adults, but it can also be done for babies. Yoga is one of the activities that can strengthen the relationship between mother and baby (bonding attachment), and it can stimulate the growth of a baby. There is not much research on the benefits of baby yoga on bonding attachment. The purpose of this study was to determine the effect of baby yoga on bonding attachment. The research method used by quasi-experimental design (quasi experiment) using the Pre Post-test Control Group Design method. This study involved 36 samples which were grouped into 2 groups with 18 samples each. Statistical test results of Pre-Post-Test Test of Baby Yoga Treatment on bonding attachment showed a significant effect with a value of p = 0.008, while for those given growth and growth stimulation did not show any significant effect with a significant value of p> 0.05 (p = 0.317). Difference test results of the difference in the results of treatment development between the baby yoga group with the growth and growth stimulation group with the results of p <0.05 (p = 0.018). Baby yoga is proven to be more effective in increasing the bonding attachment of the mother and baby.